Clinical Characteristics and Mortality of Healthcare Workers with SARS-CoV-2 infection in Mexico City - Guerrero-Torres, Lorena (Clin Infect Dis, 2020)
BACKGROUND: We evaluated the risk of death of healthcare workers (HCW) with SARS-CoV-2 infection in Mexico City during the COVID-19 pandemic and described the associated factors in hospitalized HCW compared with non-HCW. METHODS: We analyzed data from laboratory-confirmed SARS-CoV-2 cases registered from February 27-August 31, 2020 in Mexico City’s public database. Individuals were classified as non-HCW and HCW (subcategorized as physicians, nurses and other HCW). In hospitalized individuals, a multivariate logistic regression model was used to analyze potential factors associated with death and compare mortality risk among groups. RESULTS: A total of 125,665 patients were included. Of these, 13.1% were HCW (28% physicians, 38% nurses and 34% other HCW). Compared with non-HCW, HCW were more frequently female, younger and free of comorbidities. Overall, 25,771 (20.5%) were treated as inpatients and 11,182 (8.9%) deaths were reported. Deaths in the total population and in hospitalized patients were significantly higher in non-HCW than in HCW (9.9% vs 1.9%, P<.001; and 39.6% vs 19.3%, P<.001, respectively). In hospitalized patients, using a multivariate model, the risk of death in HCW in general was lower (OR 0.53) compared to non-HCW, and by specific occupation, in physicians, nurses and other HCW risk was OR 0.60, 0.29, 0.61, respectively. CONCLUSIONS: HCW represent an important proportion of individuals with SARS-CoV-2 infection in Mexico City. While the mortality risk in HCW is lower compared with non-HCW, a high mortality rate in hospitalized patients was observed in this study. Among HCW, nurses had lower risk of death compared to physicians and other HCW.